2022
DOI: 10.1111/eufm.12351
|View full text |Cite
|
Sign up to set email alerts
|

Investing for retirement: Terminal wealth constraints or a desired wealth target?

Abstract: We investigate how well different investment strategies can give pre‐retirees more certainty about their income in retirement, whilst allowing them to benefit from taking investment risk. Under an expected utility‐maximizing framework, we find that a loss aversion utility function gives a high degree of certainty about its desired wealth target and is robust to different market models. Imposing terminal wealth constraints does not improve the certainty of achieving the desired target enough to counterbalance t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…In the framework of prospect theory (PT), Blake et al (2013) and Donnelly et al (2022) treated the price of a real-life annuity at each age as the target fund throughout time and maximized the expected value of the total discounted PT utility up to retirement. The PT utility function enables the plan member to be risk seeking in the domain of losses and risk averse in the domain of gains by choosing different curvature parameters for gains and losses.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the framework of prospect theory (PT), Blake et al (2013) and Donnelly et al (2022) treated the price of a real-life annuity at each age as the target fund throughout time and maximized the expected value of the total discounted PT utility up to retirement. The PT utility function enables the plan member to be risk seeking in the domain of losses and risk averse in the domain of gains by choosing different curvature parameters for gains and losses.…”
Section: Introductionmentioning
confidence: 99%
“…Compared to CRRA preference, this strategy is more focused on achieving the specified target fund. Donnelly et al (2022) extended the framework by incorporating a stochastic non-tradable labour income process and imposing time-dependent upper and lower bounds to ensure the participant's fund value was between particular bounds at retirement. It showed that the participant's retirement outcomes are robustly centred around the target fund, and that imposing terminal wealth constraints does not improve the certainty of achieving the desired target, while it increases the chance of obtaining a lower income, which is in line with one of the findings in Basak and Shapiro (2001).…”
Section: Introductionmentioning
confidence: 99%
“…We mainly employ C to adjust the coverage or funding ratio (F 0 ). In Donnelly et al (2022), the authors make use of a similar definition for the value of a life annuity. Noting that Z T outlines a normally distributed random variable, it is clear that the expression for a T identifies a sum of τ A log-normally distributed processes.…”
Section: Benchmark and Life Annuitymentioning
confidence: 99%